Perkawinan Lari (Kawin Lari) dan Tantangan Penegak Hukum dalam Kerangka Pancasila: Elevated Marriages (Elopement) and Law Enforcement Challenges within the Pancasila Framework - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiya; Hidayah, Muhammad Arif; Muhammad Zidan Al Fath; Muhammad Asyhad Achyyarul Imam (Litera Academica Publishing, 2024)
This study examines the phenomenon of runaway marriages in Indonesia, particularly among communities with strong adherence to traditional customs. Runaway marriages are often seen as a solution for couples who lack family approval or face socio-economic pressures, but they have serious legal implications. Marriages that are not officially registered lack legal standing and negatively impact the legal rights of both the partners and any children born from such unions. Within the framework of Pancasila, runaway marriages conflict with the core values of justice, unity, and respect for the law.The study identifies challenges in enforcing laws related to runaway marriages, including inconsistencies between customary law and state law, inadequate marriage registration in remote areas, and low legal awareness among local communities. The research method involves case analysis, interviews with legal experts and community members, and a review of relevant literature. Recommendations include harmonizing customary law with state law, enhancing legal education, strengthening the role of law enforcement, and utilizing technology in marriage registration systems. These recommendations aim to align marriage practices with Pancasila values and provide fair legal protection for all individuals..